Correlation between Strategies of Translation and Politeness in Arms and the Man - Al-Mizgagi, Essam Hassan; Al-Tamemi, Jenan Abdullah (University of Science and Technology, Sana’a, 2023)
It is axiomatic that language in books and speech is full of regularities and patterns. This linguistic behavior can be reflected on translation as well when translating between English and Arabic. This study aimed to examine the potential relationship between Brown and Levinson’s (1987) politeness strategies and Vinay and Darbelnet’s (1995) translation strategies in Zaidan’s (1999) Translation of Shaw’s Arms and the Man. A quantitative method was adopted. The corpus of this study included 207 polite expressions distributed among five types of politeness strategies to be translated according to Vinay and Darbelnet`s model of translation strategies. The analysis of data was done by using SPSS (v.25) to find this potential correlation between politeness strategies and translation strategies. The findings of the study revealed that bald on record was the most frequently used strategy in both the source and the target texts. Besides, literal translation was the most frequently used strategy for rendering polite expressions. The study concluded that statistically there was no significant correlation between Brown and Levinson’s strategies of politeness and Vinay and Darbelnet’s model of translation strategies for personal and cultural reasons.
Keywords: Translation; Politeness Strategies; Drama; Corpus; Correlation